Adherence to oral hypoglycemic medication among patients with diabetes in Saudi Arabia - Ahmed, Nahid Osman; Abugalambo, Salwa; Almethen, Ghadeer Hamad (International Journal of Health Sciences, 2017)
Introduction: Diabetes mellitus is a chronic progressive disease characterized by numerous health complications. Medication adherence is an important determinant of therapeutic outcome. The objective of this study was to assess hypoglycemic medication adherence. Materials and Methods: This is a descriptive cross-sectional web-based study. The eight-item Morisky medication adherence scale was used to assess adherence. Results: A convenience sample of 290 patients with diabetes was studied; of them, 10.7% had a high adherence, 34.5% had a medium adherence, and 54.8% had a low adherence level. Adherence score was a positively and significantly correlated with age (P < 0.05). Similar significant correlation was found between adherence level and gender (P < 0.05). However, adherence was not significantly associated with diabetes duration of disease (P > 0.05) and number of hypoglycemic medications (P >0.05). Conclusion: The majority of patients with diabetes in this study had low adherence rate. The three main factors may contribute to non-adherence to medication are non-adherence to regular follow-up in diabetes clinic, non-adherence to healthy diet, and non-adherence to instruction to take medication.